Asymmetrical Pulmonary Cytokine Profiles Are Linked to Bronchoalveolar Lavage Fluid Cytology of Horses With Mild Airway Neutrophilia - Hue, Erika; Orard, Marie; Toquet, Marie-Pierre; Depecker, Marianne; Couroucé, Anne; Pronost, Stéphane; Paillot, Romain; Richard, Eric A. (Frontiers in Veterinary Science, 2020)
Few data on cytokine profiles in bronchoalveolar lavage fluid (BALF) are available for racehorses with mild/moderate equine asthma (EA); cytological diagnosis being most frequently made from only one lung. The purpose of the study was to compare cytokine mRNA expressions and protein concentrations in BALF from both lungs. As part of a larger study, 250 ml saline was randomly instilled in one lung and 500 ml in the contralateral lung of 30 clinically healthy Standardbred racehorses. This procedure was repeated 72h later, inversing the volume per lung. Cytological cut-off values for diagnosis of mild EA was neutrophils proportions > 10% when instilling 250 ml. Eleven horses that exhibited unilateral mild inflammatory cytology (i.e. normal cytology [<10% neutrophils] in the other lung) were enrolled. Protein concentrations were not significantly different between lungs, for any of the investigated cytokines. Relative mRNA expression of IL-1β (3.887 ± 0.929) and IL-10 (3.225 ± 0.516) were significantly higher in BALF from mild inflammatory lungs when compared with non-inflammatory ones (1.408 ± 0.337 and 1.488 ± 0.420, respectively); and also significantly correlated with neutrophil proportions (R = 0.45 and R = 0.58, respectively). These findings suggest that specific inflammatory response and/or regulation locally occurs within the lower airways.